2017
DOI: 10.1111/epi.13940
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoencephalographic imaging of ictal high‐frequency oscillations (80‐200 Hz) in pharmacologically resistant focal epilepsy

Abstract: SummaryObjective: Specificity of ictal high-frequency oscillations (HFOs) in identifying epileptogenic abnormality is significant, compared to the spikes and interictal HFOs. The objectives of the study were to detect and to localize ictal HFOs by magnetoencephalography (MEG) for identifying the seizure onset zone (SOZ), evaluate the cortical excitability from preictal to ictal transition, and establish HFO concordance rates with other modalities and postsurgical resection. Methods: Sixty-seven patients with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…Using MSI, Miao et al (167) showed that ictal HFOs were spatially more refined than spikes and reliably localized a propagative pattern during absence seizures in childhood absence epilepsy (167, 168). Velmurugan et al (175) just recently demonstrated the benefit of MSI in a large sample of patients with drug-resistant focal epilepsy. They were able to localize the EZ using ictal HFOs concordantly with other modalities; surgery of this identified zone performed in six patients led to seizure freedom in all of these six patients.…”
Section: Hfos Obtained From Non-invasive Recordingsmentioning
confidence: 99%
“…Using MSI, Miao et al (167) showed that ictal HFOs were spatially more refined than spikes and reliably localized a propagative pattern during absence seizures in childhood absence epilepsy (167, 168). Velmurugan et al (175) just recently demonstrated the benefit of MSI in a large sample of patients with drug-resistant focal epilepsy. They were able to localize the EZ using ictal HFOs concordantly with other modalities; surgery of this identified zone performed in six patients led to seizure freedom in all of these six patients.…”
Section: Hfos Obtained From Non-invasive Recordingsmentioning
confidence: 99%
“…Advances in magnetoencephalography (MEG) ( Migliorelli et al , 2017 ; Velmurugan et al , 2018 ; van Klink et al , 2019 ) and scalp EEG ( Kobayashi et al , 2010 ; Kramer et al , 2019 ) open a new window for the study of HFBS. The non-invasive nature of MEG and EEG enable the study of HFBS in both healthy subjects and patients ( Xiang et al , 2009 b ; Xiang et al , 2010 ; Tamilia et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Normative data may clarify the spatial variation of HFBS in the brain. For example, MEG and EEG methods, such as virtual electrodes (VE, or virtual sensors), can be used to assess brain activities at various brain areas ( Oishi et al , 2006 ; Velmurugan et al , 2018 ; van Klink et al , 2019 ). It has been shown that brain activities can be registered on to template MRI in common space, which can address the spatial variation and enable the direct comparison between patients and healthy subjects ( Douw et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have now reported the ability to record activity in the HFO frequency range from scalp electrodes, but it is unclear whether these events are the same as those recorded directly from the brain. Others have reported the ability to record HFOs with magnetoencephalography (MEG) . It is conceivable that interictal spikes associated with pHFOs will have a metabolic profile on functional magnetic resonance imaging (fMRI) that distinguishes them from interictal spikes without pHFOs, and some data are accumulating suggesting that fMRI may help to identify pHFOs noninvasively .…”
Section: Phfosmentioning
confidence: 99%
“…Others have reported the ability to record HFOs with magnetoencephalography (MEG). 31,32 It is conceivable that interictal spikes associated with pHFOs will have a metabolic profile on functional magnetic resonance imaging (fMRI) that distinguishes them from interictal spikes without pHFOs, and some data are accumulating suggesting that fMRI may help to identify pHFOs noninvasively. 33 Although we are close to accepting that pHFOs, recorded during chronic invasive monitoring, and intraoperatively, delineate the epileptogenic region for surgery, the clinical application of these EEG events for seizure diagnosis, treatment, and prediction, in the routine population of people with epilepsy, remains a hope for the future.…”
Section: Key Pointsmentioning
confidence: 99%